A novel strategy for acetonitrile wastewater treatment by using a recombinant bacterium with biofilm-forming and nitrile-degrading capability. (October 2016) - Li, Chunyan; Yue, Zhenlei; Feng, Fengzhao; Xi, Chuanwu; Zang, Hailian; An, Xuejiao; Liu, Keran
Abstract: There is a great need for efficient acetonitrile removal technology in wastewater treatment to reduce the discharge of this pollutant in untreated wastewater. In this study, a nitrilase gene ( nit ) isolated from a nitrile-degrading bacterium ( Rhodococcus rhodochrous BX2) was cloned and transformed into a biofilm-forming bacterium ( Bacillus subtilis N4) that expressed the recombinant protein upon isopropylthio-β-galactoside (IPTG) induction. The recombinant bacterium ( B. subtilis N4-pHT01- nit ) formed strong biofilms and had nitrile-degrading capability. Further testing demonstrated that biofilms formed by B. subtilis N4-pHT01- nit were highly resistant to loading shock from acetonitrile and almost completely degraded the initial concentration of acetonitrile (800 mg L −1 ) within 24 h in a moving bed biofilm reactor (MBBR) after operation for 35 d. The bacterial composition of the biofilm, identified by high-throughput sequencing, in a reactor in which the B. subtilis N4-pHT01- nit bacterium was introduced indicated that the engineered bacterium was successfully immobilized in the reactor and became dominant genus. This work demonstrates that an engineered bacterium with nitrile-degrading and biofilm-forming capacity can improve the degradation of contaminants in wastewater. This approach offers a novel strategy for enhancing the biological oxidation of toxic pollutants in wastewater. Highlights: A recombinant bacterium, Bacillus subtilis N4-pHT01- nit was established. Strain N4-pHT01- nit has two functions: biofilm formation and nitrile degradation. Strain N4-pHT01- nit had a strong resistance to loading shock from acetonitrile. Strain N4-pHT01- nit improved the degradation of acetonitrile in wastewater treatment. Strain N4-pHT01- nit was successfully immobilized in the reactor.